Performance evaluation using computational fluid dynamics combustion technique on a two-stage municipal waste incineration system - 310464 Azah Ismail (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003